Impaired CD8+ T cells in term pregnancy decidua with chronic hepatitis B virus infection. (21st August 2022) - Ma, Yanchen; Liu, Xiaoyi; Lou, Haonan; Chen, Liang; He, Weiying; Pan, Qingqing; Liao, Dandan; Li, Juanhua; Wu, Jingran; Xiong, Rongzhu; Liu, Sihua; Luo, Manling; et al.
Abstract: Problem: Hepatitis B virus (HBV) infection is more likely to develop a state of chronicity in early life, particularly mother‐to‐child transmission (MTCT) of HBV in the fetus during pregnancy. Till now, little is known about the impact of chronic HBV infection on the immune status of the maternal‐fetus interface, and the immune profile of placental lymphocytes in MTCT of HBV is poorly understood. Method of Study: Thirteen term pregnant women with chronic HBV infection (HBV‐PW) and thirteen normal pregnant women as healthy control (HC‐PW) were enrolled. The profile of placental immune cells and paired peripheral blood were analyzed by flow cytometry and immunohistochemistry. Results: Compared with HC‐PW, the frequency of CD8 + T cells from the term placenta of HBV‐PW was significantly reduced. These cells showed decreased expression of activation molecules CD69 and HLA‐DR; thus, decidual CD8 + T cells from HBV‐PW demonstrated hypofunctional signature as evidenced by significantly reduced production of IFN‐γ, as well as compromised ability of degranulation and proliferation. Conclusions: These findings supported that hypoactivated decidual CD8 + T cells might possess compromised ability in chronically HBV‐infected term pregnant women. Our study provides robust evidence for the necessity and importance of antiviral intervention in HBV‐PW to prevent MTCT of HBV.